Pengaruh Pengaruh Model Pembelajaran OIDDE Berbasis SETS Terhadap Kemampuan Pemecahan Masalah Peserta Didik pada Materi Ekologi - Silfia Hani, Ziyan; Sjaifuddin, Sjaifuddin; Taufik, Annisa Novianti (UNIB Press, 2025)
This study aimed to determine the effect of the SETS-based OIDDE model on students' problem-solving abilities in ecology material. This type of research is a quasi-experimental study with a non-equivalent control design group method involving class VIIC as the experimental class and class VIIK as the control class as samples taken randomly through random sampling techniques. The instruments used to support this research data consist of problem-solving ability test instruments in the form of essay questions, test instruments including validation questionnaire sheets, model implementation observation sheets and student response questionnaire sheets. The results of the study with a hypothesis test using Mann Whitney showed results of 0.000 <0.05 which indicated the acceptance of H1 and the rejection of H0. These results indicate that the SETS-based OIDDE model has an effect on students' problem-solving abilities.